Designing a Chatbot Application Using the Flask Framework and Rule-Based Algorithm - Haeruddin, Haeruddin; Sabariman, Sabariman; Su, Vincent (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This research aims to develop a website based chatbot application implemented at PT. International Hardware Indo using the Flask framework and Rule-Based algorithm. The application is designed to improve customer service efficiency by providing quick answers to frequently asked questions, reducing the workload of customer service, and addressing operational time constraints. The chatbot development process follows the Waterfall methodology, which includes requirements analysis, design, implementation, testing, and maintenance. The Rule-Based algorithm is employed to map user input to the company dataset through logical